Architecture, the City, and Nature: Part and Whole? - David Leatherbarrow (Oz, 2002)
Despite all the differences that immediately come to mind when natural and artificial landscapes are compared, we tend to believe that they are or should be similarly whole and entire, that each is best when characterized by unity. The same is true for individual buildings: each should be all-of-a-piece.